READING AND TEXTING WHILE WALKING: EFFECT ON GAIT INDICES IN HEALTHY YOUNG FEMALES (International Journal of Physiotherapy, 2019)
Background: Mobile phones are becoming one of the necessities now a day. Divided attention leads to affected performance in one or both tasks. Effects of such dual tasking using mobile while walking needs to be explored as the use of mobile phones during walking/stair climbing etc. are very common.Methods: 132 female students of age 18 yrs to 21 yrs were made for walking under three conditions (walking, walking and reading on mobile, walking and texting). Gait indices (step and stride length, toe out angle) were compared in all conditions using the paired t-test.Results: Step length, stride length reduced and angle of toe out increased significantly in reading during walking and texting during walking as compared to only walking (p